Rolnictwo ekologiczne w Polsce - Komorowska, Dorota (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
After Polish accession into the European Union and covering polish agriculture with Common Agricultural Policy, ecological agriculture benefits from financial aid realized within the confines of the Programme for Rural Development in the scope of agricultural and environmental programmes. As the result of the Programme realization dynamic development of ecological production has been noted, indicated by increasing number of ecological farms. The necessity of the research of economics and organization of production appeared. The aim of the article is approaching the state of polish economical agriculture development and economics of production in selected types of activity in ecological farms.